2015
DOI: 10.3171/2015.3.spine14898
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal plane lumbar intervertebral motion during seated flexion-extension radiographs of 658 asymptomatic nondegenerated levels

Abstract: OBJECT Evaluation of lumbar stability is fundamentally dependent on a clear understanding of normal lumbar motion. There are inconsistencies in reported lumbar motion across previously published studies, and it is unclear which provide the most reliable reference data. New technology now allows valid and reliable determination of normal lumbar intervertebral motion (IVM). The object of this study was to provide normative reference data for lumbar IVM and center of ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 34 publications
1
18
0
1
Order By: Relevance
“…However, free bending resulted in only approximately 0.5 mm greater translation than controlled bending to 60°. Indeed, the median ranges of translation found in this study, by all of the protocols, compare favourably with those found in a separate study of healthy volunteers 29 . However, although studies of intervertebral translation in back pain patients have concluded that it is related to age and disc height, it does not differentiate patients from controls 17,30,31 .…”
Section: Discussionsupporting
confidence: 86%
“…However, free bending resulted in only approximately 0.5 mm greater translation than controlled bending to 60°. Indeed, the median ranges of translation found in this study, by all of the protocols, compare favourably with those found in a separate study of healthy volunteers 29 . However, although studies of intervertebral translation in back pain patients have concluded that it is related to age and disc height, it does not differentiate patients from controls 17,30,31 .…”
Section: Discussionsupporting
confidence: 86%
“…Staub and colleagues reported that, for asymptomatic volunteers, with an age range of 18 to 82 years, the value of sagittal translation at each lumbar segment was: 1.9 mm at L1/L2, 2.4 mm at L2/L3, 2.7 mm at L3/4, 2.8 mm at L4/L5, and 0.5 mm at L5/S1. The sagittal plane rotation ranges were 11.0 • at L1/L2, 12.6 • at L2/L3, 13.3 • at L3/4, 14.7 • at L4/L5, and 12.8 • at L5/S1 [16]. However, there remains a gap in the current clinical knowledge about the range of segmental motion in asymptomatic participants and those with a diagnosis of LI which has not yet been studied.…”
Section: Introductionmentioning
confidence: 93%
“…Extension seems to correlate to a smaller translation and range of motion compared to flexion, where most studies describe L5S1 as least mobile. However, those studies reported different sequences and have not described motion patterns of maximum flexion and extension for L1 to S1 due to insufficient fields of view [8][9][10][11][12][13][18][19][20][21][22][23][24][25][26]. Furthermore, all studies described cumulative rotation of each individual segment at specific time points or at specific lumbar ranges of motion, which can result in missing drastic changes in intervertebral rotation between successive frames.…”
Section: Discussionmentioning
confidence: 99%